Projective synchronization analysis for BAM neural networks with time-varying delay via novel control - Sader, Malika; Wang, Fuyong; Liu, Zhongxin; Chen, Zhongxin (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, the projective synchronization of BAM neural networks with time-varying delays is studied. Firstly, a type of novel adaptive controller is introduced for the considered neural networks, which can achieve projective synchronization. Then, based on the adaptive controller, some novel and useful conditions are obtained to ensure the projective synchronization of considered neural networks. To our knowledge, different from other forms of synchronization, projective synchronization is more suitable to clearly represent the nonlinear systems’ fragile nature. Besides, we solve the projective synchronization problem between two different chaotic BAM neural networks, while most of the existing works only concerned with the projective synchronization chaotic systems with the same topologies. Compared with the controllers in previous papers, the designed controllers in this paper do not require any activation functions during the application process. Finally, an example is provided to show the effectiveness of the theoretical results.
Keywords: BAM neural networks; projective synchronization; time-varying delay; adaptive controller